Identification of spatially correlated excitations on a bending plate using the Virtual Fields Method. (4th August 2016) - Berry, Alain; Robin, Olivier
Abstract: This paper aims at identifying the autospectral density and spatial correlation functions of random excitations acting on the surface of a thin plate, from its measured vibration response. The general framework is the Virtual Fields Method (VFM), which was previously applied by the authors to the identification of deterministic excitations on plates. In the present paper, the VFM framework is extended to the case of spatially correlated excitations. It is shown that extraction of the loading power spectral density requires measuring power spectral density functions of transverse displacements and bending curvatures, which can be typically derived from contactless Laser Doppler Vibrometry measurements. The paper details the implementation of the VFM for random excitations, presents numerical simulations and experimental results for diffuse acoustic field excitation of a plate.